2012
DOI: 10.1186/1471-2105-13-202
|View full text |Cite
|
Sign up to set email alerts
|

An integrative computational approach to effectively guide experimental identification of regulatory elements in promoters

Abstract: BackgroundTranscriptional activity of genes depends on many factors like DNA motifs, conformational characteristics of DNA, melting etc. and there are computational approaches for their identification. However, in real applications, the number of predicted, for example, DNA motifs may be considerably large. In cases when various computational programs are applied, systematic experimental knock out of each of the potential elements obviously becomes nonproductive. Hence, one needs an approach that is able to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It has been confirmed that the Dof factor binding sites in subdomain B4 of the CaMV35S promoter are important and contribute to its promoter activity [46]. Although the above cis-elements are only bioinformatically predicted ones, some of them may be truly functional and they may serve as a bases for further experimental characterization and validation [47].…”
Section: Discussionmentioning
confidence: 94%
“…It has been confirmed that the Dof factor binding sites in subdomain B4 of the CaMV35S promoter are important and contribute to its promoter activity [46]. Although the above cis-elements are only bioinformatically predicted ones, some of them may be truly functional and they may serve as a bases for further experimental characterization and validation [47].…”
Section: Discussionmentioning
confidence: 94%
“…To investigate the role of miR‐181a further in LoVo and SW480 cells, we focused on the mechanism of miR‐181a overexpression in these cells. Figure A is a schematic diagram of four potential STAT1 binding elements in the promoter region of the miR‐181a gene [Deyneko et al, ] predicted by Jaspar database (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, no reasonable window size parameter as required for many programs could be suggested for our particular dataset. Therefore, we have developed a bioinformatics method that identifies combinations of heterogeneous features, like, DNA motifs, CpG islands, repeats, that are co-localized on a DNA sequence [ 10 ]. This method is based on a genetic algorithm and searches for a collection of motif combinations that exhibit high specificity for the positive dataset and localize separately on DNA sequences.…”
Section: Resultsmentioning
confidence: 99%
“…First bioinformatics analysis of promoters showing high expression in tumors revealed a so-called tusp motif apparently responsible for tumor specific activation [ 8 ]. However, further experimental data and advanced bioinformatics analysis of other groups of fragments with lower expression in tumors or with limited expression in spleen revealed that it was an oversimplification [ 9 , 10 ]. Therefore, it was required to thoroughly investigate the principles of the tumor specific transcriptional regulation and reveal contributing functional elements.…”
Section: Introductionmentioning
confidence: 99%